Environmental Awareness and Air Quality: The Mediating Role of Environmental Protective Behaviors - Kousar, Shazia; Afzal, Muhammad; Ahmed, Farhan; Bojnec, Štefan (Sustainability, 2022)
The purpose of this study is twofold: First, it tests the role of students’ environmental awareness and climate change awareness in their environmental protective behavior and environment quality (EQ). Second, it tests the mediating role of environmental protective behaviors in the association between environment behavior, climate change behavior, and environment quality. Moreover, this study utilizes climate-friendly behaviors and pro-environmental behaviors to reflect environmental protective behaviors. The stratified random sampling technique was applied to collect data through a questionnaire from a sample of 403 graduate students enrolled in Higher Education Commission-recognized private and public universities of Pakistan. This study applied partial least squares structural equation modeling (PLS-SEM) to empirically estimate the results. This study found that climate change awareness significantly and positively affects climate-friendly behavior, environmental quality, and pro-environmental behavior. Similarly, environmental awareness significantly and positively affects environmental quality and pro-environmental behavior. Moreover, pro-environmental behavior significantly affects environmental quality. Indirect results indicate that pro-environmental behavior significantly mediates between climate change awareness and environmental quality, and between environmental awareness and environmental quality. The findings of this study suggest the importance of enhancing awareness of climate- and climate change-related issues among students to save the environment. Higher education institutions should design subjects and courses that will raise environmental and climate change awareness, and expose students to climate- and environment-friendly education.